Pemanfaatan Koleksi Cetak oleh Pemustaka di Perpustakaan Umum Kabupaten Labuhanbatu - Ritonga, Nina Rahmadani; Siregar, Yusra Dewi; Yusniah, Yusniah (Lembaga Yasin AlSys, 2025)
This research aims to find out how print collections are utilized by users in the Labuhanbatu Regency Public Library, and what obstacles users face when utilizing print collections in the Labuhanbatu Regency Public Library. This kind of research uses a qualitative approach and is descriptive in nature. The research participants in this study are patrons of the library. Purposive sampling was utilised in this study to obtain the data. Three methods of gathering data were employed: documentation, interviews, and observation. Data reduction, data presentation, and decision-making are examples of descriptive analysis-based data analysis procedures. From the results of research conducted by the author, it can be concluded that the use of print collections by students is that they are more likely to use them by reading the print collection themselves in the library because the atmosphere is calm. The obstacles faced by library users are the lack of or minimal collections in the library, both aducational and entertainment books ( illustrated collections) so that they do not meet their information needs and the library’s limited operational hours.